Formulasi Self-Nanoemulsifying Drug Delivery System (SNEDDS) Ekstak Daun Pepaya (Carica papaya L.) dengan Virgin Coconut Oil (VCO) sebagai Minyak Pembawa - Metha Anung Anindhita; Nila Oktaviani (Universitas Pekalongan, 2016)
Background. Treatment with natural substances have side effect that are quite small compare to chemicals. Papaya leaves contain flavonoids that have analgesic effect. Flavonoid inhibits the production of prostaglandins. This study was conducted toformulate a papaya leave extract into Self-Nanoemulsifying Drug Delivery System (SNEDDS) technique. Method. Papaya leaves extract SNEDDS made with Virgin Coconut Oil (VCO) as oil, tween 80 as surfactant, and PEG 400 as cosurfactant. The nanoemulsion tested clarity, transmittance, emulsification time and stability. Result. Papaya leaves extract SNEDDS can be produced with VCO as oil and surfactantcosurfactan in 1:9. Keyword: papaya leaves extract, snedds, virgin coconut oil